2008
DOI: 10.1021/bc800290c
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of an Antagonist−Bombesin Analogue as Targeting Vector

Abstract: The gastrin releasing peptide receptor (GRP-R) is over-expressed on a number of tumors and cancer cell lines including pancreas, prostate, breast, gastrointestinal and small cell lung cancer (SCLC). Radiolabeled bombesin (BBN) analogues have exhibited high binding affinity and specificity to the GRP-R. A bombesin analogue with an antagonist targeting-vector at the C-terminus, DOTAaminohexanoyl-[D-Phe 6 , Leu-NHCH 2 CH 2 CH 3 13 , des Met 14 ] BBN [6][7][8][9][10][11][12][13][14] (1, "Bomproamide"), has been sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Recent preclinical studies demonstrated that GRPr antagonists may be preferable to agonists for tumor targeting, yielding high tumor uptake and long tumor washout (23,34). Our data indicated that 18 F-BAY 86-4367 behaves as an antagonist for GRPr, making this peptide promising for further evaluation in a clinical trial.…”
Section: In Vivo Characterizationmentioning
confidence: 66%
“…Recent preclinical studies demonstrated that GRPr antagonists may be preferable to agonists for tumor targeting, yielding high tumor uptake and long tumor washout (23,34). Our data indicated that 18 F-BAY 86-4367 behaves as an antagonist for GRPr, making this peptide promising for further evaluation in a clinical trial.…”
Section: In Vivo Characterizationmentioning
confidence: 66%
“…5). Different retention times of the tracers in the tumor and pancreas have also been observed for other GRPr antagonists already studied (8)(9)(10)29,30), but this was not the case for GRPr agonists (16) for which pancreas uptake was found to be high over time. Recently, Liu et al (31) have coupled NODAGA to RM1 (antagonist) and to AMBA (agonist) and labeled the 2 conjugates with 64 Cu and 18 F-AlF.…”
Section: Discussionmentioning
confidence: 76%
“…Innovative developments using agonists hybridized with other targeting units such as a v b 3 integrins or hypoxia-targeting agents such as 2-nitroimidazoles (25). The successful pharmacokinetic performance of somatostatin-based antagonistic radiotracers preclinically (6,26,27) and clinically (28) led several research groups to develop GRPr antagonists, which indeed exhibit pharmacokinetics superior to agonists (7)(8)(9)(10)(29)(30)(31)(32). Despite these promising data with the first antagonists, there is no consensus that antagonists are superior to agonists targeting the GRPr (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…During the reviewing process of this article, a paper was published describing another COOH-terminal-modified bombesin-based peptide conjugated to DOTA (40). The radiopeptide was not shown to have antagonistic properties but the tumor uptake was specific and reasonably high.…”
Section: Discussionmentioning
confidence: 99%